2020
DOI: 10.1016/j.ejca.2020.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars in oncology: Effects on economy and therapeutic innovations

Abstract: The introduction of new and innovative treatment options for cancer patients is accompanied by a tremendous increase in healthcare costs. Consequently, new financing approaches are strongly needed to reduce the burden on the healthcare system. The introduction of biosimilars e biological drugs containing the active substance of an already approved reference biological drug e can potentially relieve the burden on healthcare systems. Calculating the costs for three frequently used biosimilars, we simulated the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
9
0
3
Order By: Relevance
“…Biosimilars play a key role in reducing healthcare costs and improving patient access to life-saving therapies [ 6 ]. Results from a previous study have suggested that the use of trastuzumab biosimilars compared with originator trastuzumab may lead to annual cost savings in the range of 96 to 120 million euros (~ 11%) in a country like Germany [ 23 ]. The long-term data presented here further support trastuzumab-dkst as a valuable part of the growing biosimilar market that includes 4 other trastuzumab biosimilars approved by the FDA and EMA in recent years [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biosimilars play a key role in reducing healthcare costs and improving patient access to life-saving therapies [ 6 ]. Results from a previous study have suggested that the use of trastuzumab biosimilars compared with originator trastuzumab may lead to annual cost savings in the range of 96 to 120 million euros (~ 11%) in a country like Germany [ 23 ]. The long-term data presented here further support trastuzumab-dkst as a valuable part of the growing biosimilar market that includes 4 other trastuzumab biosimilars approved by the FDA and EMA in recent years [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having transformed certain advanced cancer into manageable chronic diseases, the success of antibody therapy has also added to the costs for healthcare systems. To make it more affordable, real-world health economic analyses indicate that application of biosimilars could save from 4.9 to 120 million Euros for each antibody treatment including Rituximab and Trastuzumab [ 28 ] .…”
Section: Evaluation Of Economic Benefitsmentioning
confidence: 99%
“…Similarly prospective annual reductions for filgrastim was 40.5 million euros, for pegfilgrastim 56.4 million euros and likewise within 95.9 and 120.5 million euros in the case of trastuzumab. 53 Transforming to multidose vials from single-dose vials has been estimated to retain an additional 59.5 million euros. 54 In another study conducted at Ministry of National Guard Health Affairs, Saudi Arabia, it was depicted that the use of filgrastim biosimilar has showed notable cost reduction annually.…”
Section: Overview Of Economic Impact and Financial Savings From Biosimilar Utilizationmentioning
confidence: 99%